Cognitive Bias Terhadap Keputusan Investasi Saham: Literasi Keuangan Sebagai Moderasi - Sukhesy Eka Putri; Wendy; Helma Malini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the influence of the relationship between Cognitive Bias on Investment Decisions which is moderated by Financial Literacy. Data was collected through a questionnaire and analyzed using Smart PLS version 3.2.9 which consists of testing the outer model and inner model. Sampling used purposive sampling, where respondents had investment experience of 1 year, ages ranging from 20 years to 43 years. This research produced 200 respondents who met the criteria. Representative, availability and anchoring have a significant positive influence on investment decisions. Likewise, financial literacy as moderation has a positive influence on investment decisions. However, financial literacy as moderation does not, namely weakening the relationship between representative, availability and anchoring.